ChemInform Abstract: Oximoaspergillimide, a Fungal Derivative from a Marine Isolate of Aspergillus sp. Issue 31 (August 2015) - Cardoso‐Martinez, Faviola; de la Rosa, Jose M.; Diaz‐Marrero, Ana R.; Darias, Jose; D'Croz, Luis; Cerella, Claudia; Diederich, Marc; Cueto, Mercedes
Abstract isolation and structure elucidation of oximoaspergillimide (I)